2007
DOI: 10.21273/hortsci.42.6.1463
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Irrigation Method and Amount of Water Application on Phytophthora and Pythium Infection and Severity of Root Rot in Highbush Blueberry

Abstract: A 2-year study was done in Oregon to determine the effects of irrigation method and level of water application on the development of root rot in northern highbush blueberry (Vaccinium corymbosum L. ‘Duke’). Plants were grown on mulched, raised beds and irrigated by overhead sprinklers, microsprays, or drip at 50%, 100%, and 150% of the estimated crop evapotranspiration requirement. Soil at the site was a silty clay loam. By the end of the first season, plants were largest wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 25 publications
2
27
1
Order By: Relevance
“…The expectation of B, B can also be computed analytically from the soil, climate and pathogen parameters, and provides a parsimonious metric of the risk posed by Pc for a given set of environmental and host conditions. 0:8, suggesting a rate of Type 2 (predicting no Pc when Pc was in fact present) errors in the range of 0-15%; (ii) examination of disease frequency on contrasting soil types in an intensively monitored Pc affected 5 95 km forest plot (Batini & Hopkins, 1972) lead to a model prediction that Pc would occur two times as frequently on clay soils than on sandy soil; observations showed that Pc actually occurred 1.9 times as frequently on clay soils than on sandy soils; and (iii) Finally, the model reproduced the near-linear increase in Pc disease severity from 20% to 60% root destruction on irrigated blueberries as the irrigation rate was increased from 0.5 to 1 to 1.5 times evaporative demand (Bryla & Linderman, 2007). The model was validated for two case studies in Western Australia and one agricultural case study in Oregon.…”
Section: Datasets Yearsmentioning
confidence: 83%
“…The expectation of B, B can also be computed analytically from the soil, climate and pathogen parameters, and provides a parsimonious metric of the risk posed by Pc for a given set of environmental and host conditions. 0:8, suggesting a rate of Type 2 (predicting no Pc when Pc was in fact present) errors in the range of 0-15%; (ii) examination of disease frequency on contrasting soil types in an intensively monitored Pc affected 5 95 km forest plot (Batini & Hopkins, 1972) lead to a model prediction that Pc would occur two times as frequently on clay soils than on sandy soil; observations showed that Pc actually occurred 1.9 times as frequently on clay soils than on sandy soils; and (iii) Finally, the model reproduced the near-linear increase in Pc disease severity from 20% to 60% root destruction on irrigated blueberries as the irrigation rate was increased from 0.5 to 1 to 1.5 times evaporative demand (Bryla & Linderman, 2007). The model was validated for two case studies in Western Australia and one agricultural case study in Oregon.…”
Section: Datasets Yearsmentioning
confidence: 83%
“…To address disease severity directly we applied the model to a Pc outbreak associated with drip-irrigation of "Duke" cultivars of blueberry Vaccinium sp. reported by Bryla and Linderman (2007). Irrigation occurs three times a week at three rates, set to provide 50%, 100%, and 150% of the estimated transpiration demand ( , 358 mm over the 5-month E max growing season).…”
Section: Model Implementation and Testingmentioning
confidence: 99%
“…Panel D shows the predicted mean pathogen extent predicted by the model for each irrigation treatment. The bars indicate the estimated range of the "vigor class" reported by Bryla and Linderman (2007) for each treatment. The results indicate that with minimal calibration the model can forecast soil moisture conditions and the resulting pathogen se-verity, given information about the cultural environment in which the crops were grown.…”
Section: Phytophthora Cinnamomi Severity With Varyingmentioning
confidence: 99%
“…[] report that drip irrigation was effective in reducing pathogens such as Colletotrichum acutatum that cause anthroids in strawberry production. However, if proper placement and frequency of drip irrigation are not maintained, there is a chance of soil borne diseases caused by Phytophthora and Pythium [ Bryla and Linderman , ; Hanson and May , ].…”
Section: Introductionmentioning
confidence: 99%